Farinha de baru (Dipteryx alata) na dieta de bezerros leiteiros - Lucas Gomes Vieira (2023)
The baru is a native fruit of the Cerrado, rich in carbohydrates and energy, which has high productivity, characteristics that contribute to the inclusion of its by-product in ruminant diets. The performance, consumption and ingestive behavior of dairy calves fed with different levels of baru meal (Dipteryx alata. Vog) replacing corn in the solid diet were evaluated. Sixteen newborn calves Holstein X Gir with initial body weight average of 33± 5.78 kg were used. The treatments were different levels of replacement of corn by baru meal in the concentrate: 0%, 25%, 50% and 72%. Total dry matter intake, concentrate and roughage intake, and weight gain of the animals were evaluated. There was no difference in weight gain between treatments in the five weeks evaluated (13.7kg). The total dry matter intake (DMI), average intake of concentrate (CO) and roughage (VO) showed similar means between treatments (114.85g DM/day, 102.8g DM CO/day, 12.21g DM VO/ day). The inclusion of baru meal linearly increased the consumption of crude protein, mineral matter, ether extract and non-fiber carbohydrates. There was a change in the time spent for concentrate consumption, with a time of 75.92 min/day being observed with 67% replacement. An economic analysis was carried out and the treatment with 50% replacement presented a higher cost of daily food but a lower cost per kilo of gain. The inclusion of baru meal up to 72% replacing corn in the diet does not change the productive performance of calves in the pre-weaning phase, however, the inclusion of 50% provides a better economic return.